2015
DOI: 10.1007/s00376-014-4100-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure and propagation of a simulated squall line on 14 June 2009

Abstract: A squall line on 14 June 2009 in the provinces of Jiangsu and Anhui was well simulated using the Advanced Regional Prediction System (ARPS) model. Based on high resolution spatial and temporal data, a detailed analysis of the structural features and propagation mechanisms of the squall line was conducted. The dynamic and thermodynamic structural characteristics and their causes were analyzed in detail. Unbalanced flows were found to play a key role in initiating gravity waves during the squall line's developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…It is important to note that sea level rise extension from the Indian Ocean to the Java Sea implies that driving forces over the near-surface level at the atmosphere are strongly connected with the surface ocean component. The eastward propagation of Kelvin might also increase the sea level from the Indian Ocean to the Java Sea wave, which resembles prior studies mentioned that its various phase speeds of propagation from 1.3 to 1.7 m s −1 [ 26 , 27 ]. The eastward propagation was developed by regular zonal wind strengthening around 20–90 days.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…It is important to note that sea level rise extension from the Indian Ocean to the Java Sea implies that driving forces over the near-surface level at the atmosphere are strongly connected with the surface ocean component. The eastward propagation of Kelvin might also increase the sea level from the Indian Ocean to the Java Sea wave, which resembles prior studies mentioned that its various phase speeds of propagation from 1.3 to 1.7 m s −1 [ 26 , 27 ]. The eastward propagation was developed by regular zonal wind strengthening around 20–90 days.…”
Section: Methodssupporting
confidence: 66%
“…2 c). This sea level rise propagation was related to a cyclonic vortex, with the core existing precisely over the equatorial line indicated by the streamlined wind at the surface level, which was also strengthened by the Kelvin wave [ [28] , [29] , [30] ] and initiated from equatorial zone of Indian Ocean [ 26 , 27 ]. Those sequential sea level rises were confirmed by station data recorded in several locations, such as southern Sumatra, Sunda Strait, and southern Central Java, on 22 May, 22 May, and May 25, 2020, respectively ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 0430 UTC (Figure 10a), the distribution of vorticity and divergence showed a clear positive and negative change below the height of 2 km, and they propagated from west to east. The vorticity was located one-quarter of a wavelength behind the divergence, showing the characteristics of a gravity wave (Li, 1978;Liu et al, 2015) [22,23]. In terms of the wind field, westerly wind dominated above the level of 2 km, while it was controlled by weak easterly wind below the level of 1 km.…”
Section: Initiation Mechanism Of Convective Cells In the Plain Regionmentioning
confidence: 99%
“…[18] A combination of wave ducting and the wave-CISK mechanism has successfully explained the propagation and maintenance of convection systems. [19,20] Subsequently, many studies have focused on the effects of gravity waves on convection; for example, Liu et al [21] investigated the role of gravity waves in the development of squall lines and found that a combination of gravity waves and cold pool outflow maintained the propagation and development of squall lines. Su and Zhai [22] discovered us-ing high-resolution numerical models that gravity waves and convergence lines together promoted convection initiation.…”
Section: Introductionmentioning
confidence: 99%